Identification of Quantitative Trait Loci Determining Vegetative Growth Traits in Coffea canephor - Priyono Priyono; Ucu Sumirat; Crouzillat Crouzillat (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2011)
Recently the use of molecular markers has been successfully applied for some crops. For coffee, new opportunities have been opened since Nestlé R&D Centre in collaboration with ICCRI completed the first genetic map of Coffea canephora. This study was aimed both to evaluate the phenotypic trait and also to identify the quantitative trait loci (QTLs) controlling the vegetative growth in Robusta coffee. Present study used three C. canephora populations and six genetic maps developed based on these populations using simple sequence repeats (SSRs) and single nucleotide polymorphisms (SNPs) markers. A total of 17 different quantitative data were used for the detection of QTLs on each of three populations. Present result showed that most of these traits were not heritable. The nine vegetative traits have been identified and distributed over seven different linkage groups. Due to some QTLs determining one given trait were overlapping on the same linkage group and were coming from the same favourable parent, a total of 19 QTLs detected for vegetative traits might finally be considered as only 12 QTLs involved. However, only two of them were shared for different traits. One involved for the number/length of primary branches and width of the canopy while the other for length of internodes and width of canopy. These two QTLs might determine the size of the tree canopy in this species. Key words: Coffea canephora, heridity, quantitative trait loci (QTLs), vegetative growth.